Spatial Aspects of Schools Provision from the Point of View of Users. Results of a Parent/Pupil Survey in Schleswig-Holstein - Diller, Christian; Frank, Keno (Raumforschung und Raumordnung | Spatial Research and Planning, 2014)
In this article the point of view of users, namely parents and pupils, regarding the spatial aspects of educational planning are taken into account. In view of increased educational competition, pressure to achieve in schools and an ever broader and more sophisticated range of educational opportunities, what role do spatial aspects actually play in pupils’ and their parents’ attitudes to education?Is the spatial proximity of schools actually still important, when one considers the general increase in the scope of children’s activities? In an empirical study of two districts of Schleswig-Holstein the aspect of physical distance is identified as a theme in numerous respects. The objective school journey distances are examined, as well as the latent importance of the physical proximity of the place of residence to the location of the school for the educational success of the child. Also examined are the contacts between pupils and the social involvement of the parents in the school; the concrete importance of the physical proximity of the home to the school when making a decision about the choice of school location; and the home to school journey distances which are considered reasonable for the pupils. Furthermore various aspects of the choice of transport are also examined.Finally of interest is also the research methodology question regarding what explanatory content latent attitude variables have in comparison to variables which relate to concrete decision-making situations.
Keywords: School development planning; Social infrastructure; Welfare provision; Public welfare provision; Demographic change; Schleswig-Holstein